2013
DOI: 10.1097/icu.0b013e32835f8ec0
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and systemic safety of bevacizumab and ranibizumab in patients with neovascular age-related macular degeneration

Abstract: Although rare, adverse events with off-label use of bevacizumab are more common than with ranibizumab. Continued study into long-term safety of the two agents is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 112 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…4 Many cases can be treated successfully with topical or local corticosteroids, although more severe cases are often presumed infectious and treated as such. 4,5 There seems to be an underlying rate of intraocular inflammation with all anti-VEGF drugs, and clusters of higher rates of inflammation may also occur. [6][7][8][9][10][11] The mechanism of intraocular inflammation after anti-VEGF remains unknown; suggested mechanisms have included immune response to the drug itself, other protein byproducts within the medication, or differences in pH, whereas mechanisms of inflammation clusters have been attributed to silicone oil residues, silicone/protein aggregates, or endotoxins.…”
Section: Etiologymentioning
confidence: 99%
“…4 Many cases can be treated successfully with topical or local corticosteroids, although more severe cases are often presumed infectious and treated as such. 4,5 There seems to be an underlying rate of intraocular inflammation with all anti-VEGF drugs, and clusters of higher rates of inflammation may also occur. [6][7][8][9][10][11] The mechanism of intraocular inflammation after anti-VEGF remains unknown; suggested mechanisms have included immune response to the drug itself, other protein byproducts within the medication, or differences in pH, whereas mechanisms of inflammation clusters have been attributed to silicone oil residues, silicone/protein aggregates, or endotoxins.…”
Section: Etiologymentioning
confidence: 99%
“…In human studies, Avery et al 96 found that the systemic exposure after the third monthly intravitreal injection was 13-fold greater for aflibercept and 70-fold greater for bevacizumab than for ranibizumab. Another report reviewed differences in both ocular and systemic safety between intravitreal bevacizumab and ranibizumab in the setting of neovascular AMD 91. Serious adverse events associated with either bevacizumab or ranibizumab injections are generally rare.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…The ocular route of administration is classified as "Very High" risk in the risk assessment framework not because this route is particularly associated with the generation of antibody responses, but rather because the consequences of ATA or anti-HCP antibody development in the eye can be quite serious. Immune responses within the eye can result in inflammation and/or altered intraocular pressure, which may lead to retinal damage and impaired vision (Johnson and Sharma, 2013).…”
Section: Route Of Administrationmentioning
confidence: 99%